QUO VADIS UNDANG-UNDANG NO. 5 TAHUN 1986 TENTANG PERADILAN TATA USAHA NEGARA JIS. UNDANG-UNDANG NO 51 TAHUN 2009 DAN KOMPETENSI PERADILAN TATA USAHA NEGARA DALAM UU. NO. 30 TAHUN 2014 TENTANG ADMINISTRASI PEMERINTAHAN - Kartika Widya Utama (Masalah-Masalah Hukum, 2015)
Any change in the legislation, always cause changes / shifts in legal actions and legal consequences arising in the implementation and enforcement process .Act No. 30 of 2014 on Government Administration to bring a change in the term of authority Administrative Court in a dispute over the administration of the State . Needs to be studied more deeply how the legal consequences that would occur as a result of differences in the rules in the Act No. 30 of 2014 with Act No. 5 of 1986 .Law No.30 Year 2014 has expanded the authority of the Administrative Court , the extension of this authority should need to be addressed carefully in order not to create legal uncertainty in practice . The government should immediately issue regulations governing the implementation of the new judicial procedure related to some fundamental changes in the Law on Government administration .